Evaluasi Kepuasan Pengguna Website Menggunakan Framework PIECES: Studi Pada Pemerintah Kabupaten Maluku Barat Daya - Malioy, Rimes Jopmorestho; Sediyono, Eko; Maria, Evi (Jurnal Sistem Informasi Bisnis, 2024)
This research aims to evaluate the local government website of Southwest Maluku Regency using the PIECES framework, to determine the level of user satisfaction. The method used in this research is quantitative descriptive. The questionnaire was distributed to the public and State Civil Apparatus (ASN) who are users of the regional government website. The total sample for this research was 150 respondents. Measurements were carried out using a Likert scale. The research results found that users were very satisfied with the information & data presented on the local government website. In terms of performance, economics, control & security, users feel satisfied when using the website. In terms of service, users are very satisfied if the website is developed and improved further. Meanwhile, in terms of efficiency, users want additional website features, namely the online complaint feature. Overall, the average user satisfaction level is 3.99 in the satisfied category. Additional testing using PageSpeed Insight and Qualys found that the government website's performance was still low, with a score of 76. Meanwhile, in terms of security, additional testing found that the website was very good with an A+ score. The results of this research become evaluation material for website managers, namely the Southwest Maluku Regency Communication and Information Service, to make improvements to the website from several aspects that have been assessed, to increase the level of user satisfaction.